Evaluation and Management of the Emergency Department Headache - Filler, Levi; Akhter, Murtaza; Nimlos, Perrin (Seminars in Neurology, 2019)
The acute headache in the emergency department (ED) poses a diagnostic dilemma that may overwhelm providers attempting to weigh the cost of advanced workups against the risk of missing serious pathology. While the majority of headache concerns are benign primary headache disorders, identifying life-threatening secondary causes of headache—which may be broadly categorized into structural, infectious, and vascular causes—is the primary focus of evaluation in the ED. Secondary headaches are associated with a high morbidity and mortality, and require strict scrutiny of the history and physical examination to adequately risk-stratify patients. Innovative and emerging technologies may further assist providers in the diagnosis of headache, and challenge previous gold-standard diagnostic evaluations. Herein, we present a general overview of the workup and management of headaches in the ED, with a special section for diagnostic considerations in evaluating for acute meningitis, subarachnoid hemorrhage, and acute angle-closure glaucoma.
Keywords: acute headache; emergency department; secondary headache; malignant pathology